Experimental evaluation of the high-grade properties of recycled concrete aggregates and their application in concrete road pavement construction. (December 2019) - Kox, S.; Vanroelen, G.; Van Herck, J.; de Krem, H.; Vandoren, B.
Abstract: In Flanders, up to 20% of the coarse natural aggregates in concrete mixtures for certain applications in road pavement construction may be replaced by high-grade recycled concrete aggregates (RCA). The RCA and resulting recycled aggregate concrete (RAC) have to comply with the high-grade criteria specified in the Flemish 'Standard Tender Specifications 250 version 3.1' and require extensive and time-consuming testing procedures, leading to reluctance in effectively prescribing and using recycled aggregates. The objective of this case study is therefore to draw up practical recommendations for the rapid identification of high-grade RCA. RCA from different sources are investigated and subsequently used in two concrete road pavement construction applications, namely linear elements and applications within the Flemish concrete construction class 'BF' (i.e. cycle paths, footpaths and agricultural roads). The experimental results indicate that the aggregate density along with the water content appears to be good predictors for the resistance to abrasion (i.e. the Los Angeles coefficient). The aggregate experiments also show that, in order to fulfill the aforementioned tender specifications criteria, it is important to demolish and store the source material in such a way that no contamination with non-concrete materials (such as ceramics) takes place, maintaining a high specific density. The experiments on RAC, on the other hand, show that an aggregate replacement rate of up to 40% of the coarse fraction has no detrimental effect on the mechanical and durability performance. When comparing the results of both aggregate and concrete experiments, they show that freeze–thaw resistance of the concrete aggregates has slight to no impact on the freeze–thaw resistance of the concrete.